Possible Association between the Lack of Regular Physical Activity with Tinnitus and Headache: Cross-sectional Study - Bazoni, Jéssica Aparecida; Dias, Ana Carolina Marcotti; Meneses-Barriviera, Caroline Luiz; Marchiori, Luciana Lozza de Moraes; Teixeira, Denilson de Castro (International Archives of Otorhinolaryngology, 2019)
Introduction Physical inactivity is an important risk factor for many aging-related symptoms. Studies suggest that physical activity may help to relieve tinnitus and headache.Objective To investigate the presence of tinnitus and headache in elderly individuals by associating it with the lack of regular physical activity.Methods A cross-sectional study including elderly individuals who live independently. The practice of physical activity and the complaints of headache and of tinnitus were checked by means of a questionnaire with objective questions. The statistical analysis was performed using the chi-squared test and relative risk, and a multiple logistic regression model was used to determine how well each factor predicted headache while controlling for each of the other factors.Results Based on a sample of 494 subjects, it was found that 213 (43.11%) complained of tinnitus. Among the complainants, 97 (45.53%) practiced physical activity regularly. We have confirmed associations between headache with lack of physical activity among elderly individuals with tinnitus (p = 0.0440). It was also observed that certain factors, such as male gender and tinnitus, are independent factors for the complaint of headache.Conclusion We have found that headache could be a symptom related to the lack of regular physical activity among elderly individuals with tinnitus.
Keywords: tinnitus; aging; exercise; headache